NK cell tolerance as the final endorsement of prenatal tolerance after in utero hematopoietic cellular transplantation - Alhajjat, Amir M.; Lee, Amanda E.; Strong, Beverly S.; Shaaban, Aimen F. (Frontiers in Pharmacology, 2015)
The primary benefits of in utero hematopoietic cellular transplantation (IUHCT) arise from transplanting curative cells prior to the immunologic maturation of the fetus. However, this approach has been routinely successful only in the treatment of congenital immunodeficiency diseases that include an inherent NK cell deficiency despite the existence of normal maternal immunity in either setting. These observations raise the possibility that fetal NK cells function as an early barrier to allogeneic IUHCT. Herein, we summarize the findings of previous studies of prenatal NK cell allospecific tolerance in mice and in humans. Cumulatively, this new information reveals the complexity of the fetal immune response in the setting of rejection or tolerance and illustrates the role for fetal NK cells in the final endorsement of allospecific prenatal tolerance.